Biofilm production by Haemophilus influenzae and Streptococcus pneumoniae isolated from the nasopharynx of children with acute otitis media - Quentin Vermee (BMC Infectious Diseases, 2019)
Abstract Background Biofilm production by Haemophilus influenzae and Streptococcus pneumoniae has been implicated in the pathogenesis of otitis media, mainly in chronic and recurrent cases. We studied the “in vitro” biofilm production by these 2 species isolated alone or together from the nasopharynx of children with acute otitis media. Methods The studied strains were from 3 pneumococcal conjugate vaccine (PCV) periods: pre-PCV7, post-PCV7/pre-PCV13 and post-PCV13. A modified microtiter plate assay with crystal violet stain was used to study the biofilm production of 182 H. influenzae and 191 S. pneumoniae strains. Results Overall, 117/181 (64.6%) H. influenzae and 128/191 (66.8%) S. pneumoniae strains produced biofilm. The proportion of biofilm-producing H. influenzae strains was greater with than without the isolation of S. pneumoniae in the same sample (75.5% vs 52.3%, p = 0.001). Conversely, the proportion of biofilm-producing S. pneumoniae strains was not affected by the presence or not of H. influenzae (66.3% vs 67.4%). S. pneumoniae serotypes 6B, 15B/C, 19A, 35F and 35B were the better biofilm producers (80%). Serotypes 11A, 14, 15A, 19F and 19A were more associated with H. influenzae biofilm-producing strains. Overall, 89/94 (94.6%) of cases with combined isolation showed biofilm production by S. pneumoniae or H. influenzae. Conclusion This study emphasizes the high proportion of biofilm production by H. influenzae and S. pneumoniae strains isolated from the nasopharynx of children with acute otitis media, which reinforces the results of studies suggesting the importance of biofilm in the pathogenesis of acute otitis media.